Estimating the effect of healthcare-associated infections on excess length of hospital stay using inverse-probability weighted survival curves - Pouwels, KB; Vansteelandt, S; Batra, R; Edgeworth, J; Wordsworth, S; Robotham, JV (Oxford University Press, 2020)
Background Studies estimating excess length of stay (LoS) attributable to nosocomial infections have failed to address time-varying confounding, likely leading to overestimation of their impact. We present a methodology based on inverse probability-weighted (IPW) survival curves to address this limitation.